Generalized approximate message passing based SrCMA satellite receiver - Le YU; Lidong ZHU; Liang JIN; Jiali LI; Yilun LIU; Cheng GUO (Dianxin kexue)
In order to satisfy the requirements of the transmission rate and spectrum resource for various terminals and equipment in the satellite internet, a generalized approximation-based message passing optimization satellite receiver was designed.Considering the multi-user detection in the satellite network using the non-orthogonal multiple access, a factor graph was established based on the graph model, and the factor graph was used to analyze the message passing model of the system and a message passing algorithm was proposed.Based on the generalized approximate message passing method, the complexity of the traditional multi-user detector based on message passing was further reduced.Under satellite channel condition, generalized approximate messaging satellite receivers were studied.The simulation results show that the proposed algorithm can effectively solve the signal coexistence problem of multi-users, and reduce the computational complexity of the algorithm.